6(d-6)=4(d-60)+2d

Simple and best practice solution for 6(d-6)=4(d-60)+2d equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(d-6)=4(d-60)+2d equation:


Simplifying
6(d + -6) = 4(d + -60) + 2d

Reorder the terms:
6(-6 + d) = 4(d + -60) + 2d
(-6 * 6 + d * 6) = 4(d + -60) + 2d
(-36 + 6d) = 4(d + -60) + 2d

Reorder the terms:
-36 + 6d = 4(-60 + d) + 2d
-36 + 6d = (-60 * 4 + d * 4) + 2d
-36 + 6d = (-240 + 4d) + 2d

Combine like terms: 4d + 2d = 6d
-36 + 6d = -240 + 6d

Add '-6d' to each side of the equation.
-36 + 6d + -6d = -240 + 6d + -6d

Combine like terms: 6d + -6d = 0
-36 + 0 = -240 + 6d + -6d
-36 = -240 + 6d + -6d

Combine like terms: 6d + -6d = 0
-36 = -240 + 0
-36 = -240

Solving
-36 = -240

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| -7x+(-7x-30)=36 | | 9mn/4n | | -2x^2+6x+8=12 | | -1=-5-4s | | 18z^3+9z^2-50z-25=0 | | x^2=y^2-20.25 | | 4(-5x+35)-x+7=0 | | 5x/2-8=2x-7/6 | | 2s+7=-5s | | 10a-83=203 | | X=(18+8) | | x=(x)(x) | | 34-2x=80 | | X^2-76+1380=0 | | 258=175-w | | 250=10e | | -2(2q-4)=10q-20 | | 11y+12=45 | | Sin(x)=-0.62 | | 9-7p=8 | | 09-7p=8 | | x+18+3*x=74 | | 8w+2=90 | | 11/h-5=7/5-h | | 68x=y-2875 | | 3x-(3x^2-7x)+8x^2= | | 11p+12=45 | | 2-(13-m)=-(m-19)-6 | | 8k-8=24 | | 1.5a=-12 | | -5.9=w+6.1 | | 9x+-9+9x= |

Equations solver categories